Intracellular distribution of microinjected antisense oligonucleotides. - Leonetti, J P (1991)
Antisense oligomers constitute an attractive class of specific tools for genetic analysis and for potential therapeutic applications. Targets with different cellular locations have been described, such as mRNA translation initiation sites, pre-mRNA splicing sites, or the genes themselves. However the mechanism(s) of action and the intracellular distribution of antisense oligomers remain poorly understood. Antisense oligomers conjugated with various fluorochromes or with BrdUrd were microinjected into the cytoplasm of somatic cells, and their cellular distribution was monitored by fluorescence microscopy in fixed and nonfixed cells. A fast translocation in the nuclei and a concentration on nuclear structures were observed whatever probe was used. Nuclear transport occurs by diffusion since it is not affected by depletion of the intracellular ATP pool, temperature, or excess unlabeled oligomer. Accumulation of the oligomers in the nuclei essentially takes place on a set of proteins preferentially extracted between 0.2 M and 0.4 M NaCl as revealed by crosslinking of photosensitive oligomers. The relationship between nuclear location of antisense oligomers and their mechanism of action remains to be ascertained and could be of major interest in the design of more efficient antisense molecules.